Tổng hợp, cấu trúc và hoạt tính sinh học của một vài phức chất cis-đicloro(safrol)(amin)platin(II) - Thanh Chi, Nguyễn Thị; Đà, Trần Thị (Vietnam Journal of Chemistry, 2014)
Three complexes of platinum(II) including cis-[Pt(Saf)(piperridine)Cl2] (P4), cis-[Pt(Saf) (aniline)Cl2] (P5), cis-[Pt(Saf)(o-toluidine)Cl2] (P6) have been synthesized. The structure of the complexes have been determinded by elemental analysis, molar conductivity, API MS, IR, Raman, electronic and 1H NMR spectra studies. The biological test shown that complexes P4 exhibit antimicrobial activity on C.albicans, P5 on  E. coli bacterium and F. oxysporum. P4 exhibit inhibitor activity on Hep-G2 cancel cell, P6 on Hep-G2 and RD cancel cell at concentration 1.7 -3.2 µg/ml.